(3OjhGf GdCOHs - (3ESMGb Hf EHQGgje Hf GdMSjf GdaGQGHqj, CHh EHQGgje, J (B350 (3g` s ((3CMeO Hf GdHUjQ s)
(3BNQgG (B:s
(3ef HGH aGYd HaJM GdYjf (B: (3Y (B: (3GdWGHY dZI ai GdWGHY b(B: (3GdOGfb d(B: (3GdJGHd hGMO GdJhGHd GdWGLf dZI ai GdWjLf hcdGgeG ehdO dELJeGY GdWGA hGdLje ai cdeI hGMOI , hPdc dGjchf ai cdGege GdCUdi BNQ GdLRA GdChd hjJhdg ai GdKGfi HGH aGYd s
(3fSNI JJab ai ChdgG eY Chd fSNI edi edc (B-(3WgQGf (B345 (3HGNJdGa ai HYV GdCdaGXs
(3HChdgG Jedc bOjes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B293s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GddZIs